Therapeutic Approach with PCSK9 Inhibitors for Effective Cardiovascular Risk Reduction in Diabetes - Arrieta, Francisco; Iglesias, Pedro; Aguilar, Manuel; Mata, Pedro; Pedro-Botet, Juan (Cardiology and Cardiovascular Medicine, 2020)
Abstract not available in the source database.